DIFFERENT TYPES OF HEADACHES AND RELATED FACTORS IN HOSPITALIZED PREGNANT WOMEN: Pharmaceutical Sciences-Medicine - JALILIAN, NASRIN; HEMATTI, MARYAM; ZANGENEH, MARYAM (International Journal of Life Science and Pharma Research, 2022)
Headache is one of the most common complaints in pregnant women. Different conditions including vascular disorders and thrombosis can have role in headache. The objective of this study was to assess the frequency of different types of headaches during pregnancy among hospitalized patients. In this descriptiveanalytic study, 616 pregnant women who presented with headache from 2009 to 2015 and were admitted to our university hospital were studied. A checklist was designed which included demographic data, the frequency of different types of headaches, radiologic evaluation, frequency of photophobia, nausea, vomiting, fever, neck stiffness, decreased consciousness level, convulsions, blurred division, palsy, muscular stiffness, vertigo, epigastric pain, and fatigue were recorded using the medical records. The data were analyzed using the SPSS software. Mean age of the patients was 30.03 years and mean gestational age was 32.63 weeks. Mean gravity was 2.30 and mean parity was 0.09. The most frequent type of headache was related to preeclampsia seen in 430 patients (70%) and the least frequent type was hemorrhaging arteriovenous malformation (AVM) or aneurysm (each was documented in five patients (0.8%)). Due to lack of enough studies about headaches during pregnancy, the presented results can be considered as a basis for Future studies.